Survival of Salmonella anatum Heated in Various Media - Moats, W. A. (1971)
Survival of Salmonella anatum heated at 55 C for 35 min was determined in solutions of various chemical constituents of foods including salts, carbohydrates, amino acids, peptides, nucleic acids, gums, and stabilizers and compared with survival in 0.1 m phosphate buffer (pH 7.0). Commercially sterilized whole milk gave the most protection against heat. Trypticase Soy Broth, various peptide mixtures, and some amino acids gave substantial protection. Results with carbohydrates were variable, with mannitol, sucrose, and rhamnose providing substantial protection and glucose decreasing heat resistance. A few other substances, cysteine, glutathione, and sodium citrate, also decreased heat resistance. Pure proteins had little effect. Results show that water activity is of little significance under the test conditions. Protection from heat probably results from complexing of substances with heat-sensitive proteins in the cells. Autoclaved milk should not be considered equivalent to raw milk for studies of survival of bacteria during heating.